2016
DOI: 10.1038/nsmb.3211
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA LINP1 regulates repair of DNA double-strand breaks in triple-negative breast cancer

Abstract: Long noncoding RNAs (lncRNAs), which are transcripts that are larger than 200 nucleotides but do not appear to have protein-coding potential, play critical roles during tumorigenesis by functioning as scaffolds to regulate protein-protein, protein-DNA or protein-RNA interactions. Using a clinically guided genetic screening approach, we identified (lncRNA in Non-homologous end joining [NHEJ] pathway 1) as a lncRNA that is overexpressed in human triple-negative breast cancer. We found that LINP1 enhances double-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
217
2
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 246 publications
(242 citation statements)
references
References 40 publications
5
217
2
3
Order By: Relevance
“…Alternatively, CUPID1 might be acting as an RNA scaffold for DNA-repair complexes similarly to LINP1, which has recently been shown to promote NHEJ by acting as a RNA scaffold for Ku70-Ku80 and DNA-PKcs. 35 In summary, we have shown that breast cancer risk variants at 11q13 might regulate two lncRNAs, in addition to CCND1, and provide evidence that reduced expression of the lncRNAs mediates risk by favoring a switch from HRR to NHEJ DSB repair. Importantly, these data are consistent with observations in breast tumors whereby a HR mutation signature is associated with increased structural variants presumably caused by DSB repair through error-prone pathways.…”
Section: Discussionmentioning
confidence: 66%
“…Alternatively, CUPID1 might be acting as an RNA scaffold for DNA-repair complexes similarly to LINP1, which has recently been shown to promote NHEJ by acting as a RNA scaffold for Ku70-Ku80 and DNA-PKcs. 35 In summary, we have shown that breast cancer risk variants at 11q13 might regulate two lncRNAs, in addition to CCND1, and provide evidence that reduced expression of the lncRNAs mediates risk by favoring a switch from HRR to NHEJ DSB repair. Importantly, these data are consistent with observations in breast tumors whereby a HR mutation signature is associated with increased structural variants presumably caused by DSB repair through error-prone pathways.…”
Section: Discussionmentioning
confidence: 66%
“…Our results were consistent with the expression trends of the sequencing data. LINP1 significantly overexpressed in basal breast cancer and regulated repair of DNA breaks [19]. LINC01011 expressed differentially in intrahepatic cholangiocarcinoma and adjacent normal tissues [20].…”
Section: Discussionmentioning
confidence: 99%
“…Critical to NHEJ function is protein phosphorylation by both DNA-PKcs and the related ATM, which phosphorylate each other and other components of the DDR to regulate NHEJ and other cellular processes. Recently, noncoding RNAs have also been shown to regulate DSB repair (Lees-Miller, Beattie, & Tainer, 2016; Zhang et al, 2016), adding an additional level of largely unexplored regulation to the system.…”
Section: Dna Double-strand Break Responsesmentioning
confidence: 99%